Books as trenches. The Servicio de Lecturas del Soldado of the University Library of Zaragoza during the Civil War (1936-1939) - Blanco Domingo, Luis (Revista General de Información y Documentación, 2017)
The Servicio de Lecturas para el Soldado was an organization promoted by Miguel Artigas from the University Library of Zaragoza during the Civil War (1936-1939) as one more instrument that contributed to the military triumph of the rebel forces. The objective of this work is to analyze its fundamental aspects: the difficult cohabitation with the ordinary activity of the university library; the evolution of its operation and scope; the role of librarians; and the results obtained, framed within a context in which war emergencies coexist and a peculiar symbiosis between the concepts of therapeutic and guided reading.
Keywords: Servicio de Lecturas para el Soldado; Civil War; Rebel forces; Miguel Artigas; University Library of Zaragoza; Javier Lasso de la Vega; Aurea Javierre; Guided reading